1989
DOI: 10.1002/1097-4679(198907)45:4<575::aid-jclp2270450412>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The utility of MMPI subtle, obvious scales for detecting fake good and fake bad response sets

Abstract: The MMPI was administered twice to 40 graduate students to determine the utility of the Weiner subtle and obvious scales (D, HY, PD, PA, MA) for estimating how fake good and fake bad response sets might influence full scale scores. The first time, the MMPI was administered under standard conditions. Subjects then were divided randomly into two groups: fake good (complete MMPI for job application) and fake bad (qualify for psychotherapy). There were significant multivariate test effects (standard vs. response s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The F-r data were complex and only partially satisfied H4. We believe that this occurred because we tested a normal sample, and thus the “floor effect” described by Peterson et al (1989) was high (honest respondents endorsed so few psychopathology-related items that, when asked to fake good, few differences could be noted). The results also stressed that speed induced FGs to significantly improve their self-representation in the L-r and K-r scales.…”
Section: Discussionmentioning
confidence: 99%
“…The F-r data were complex and only partially satisfied H4. We believe that this occurred because we tested a normal sample, and thus the “floor effect” described by Peterson et al (1989) was high (honest respondents endorsed so few psychopathology-related items that, when asked to fake good, few differences could be noted). The results also stressed that speed induced FGs to significantly improve their self-representation in the L-r and K-r scales.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, test-takers possessing relevant job knowledge and/or experience have been found to be better able to fake than inexperienced test-takers (Frei, Griffith, Snell, McDaniel, & Douglas, 1997;Vasilopoulos et al, 2000). Our results for familiarity are also consistent with research that shows that people can better fake more obvious (transparent) items than more subtle ones in personality inventories (e.g., Peterson, Clark, & Bennett, 1989;Posey & Hess, 1984). Apparently, possessing relevant schemata of the job domain and its requirements provides candidates with cues that make faking somewhat easier Christiansen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical use of the Wiener and Harmon (Wiener, 1948) Subtle and Obvious scales has had a long and controversial history. Originally developed to detect deviant test-taking attitudes in the MMPI, the clinical utility of the Subtle and Obvious scales is questionable, as research that used the original MMPI clearly has shown (Dannenbaum & Lanyon, 1993;Herkov, Archer, & Gordon, 1991;Peterson, Clark, & Bennett, 1989;Rogers, 1983;Schretlen, 1988Schretlen, , 1990Wrobel & Lachar, 1982) and MMPI-2 (Berry, Baer, & Harris, 1991;Boone, 1994a;Butcher, 1989;Graham, Watts, & Timbrook, 1991;Herkov, Gordon, Gynther, & Greer, 1994;Peterson et al, 1989;Timbrook, Graham, & Watts, 1993;Weed, Ben-Porath, & Butcher, 1990). To summarize, the Subtle and Obvious scales "have led to ambiguous identification of faking" (Dubinsky, Gamble, & Rogers, 1985, p. 67) and may "attenuate the validity of the Full Scale by introducing variance that is not related to variance in the criterion measure" (Weed et al, 1990, p. 12).…”
mentioning
confidence: 99%